Virginia Cyber Navigator Internship Program (VA-CNIP): Service Learning in Local Election Security (Journal of The Colloquium for Information Systems Security Education, 2023)
A coalition of Virginia universities, in partnership with the Virginia Department of Elections (ELECT), launched the Virginia Cyber Navigator Internship Program (VA-CNIP) – an innovative educational program to develop future cybersecurity professionals to protect the election infrastructure. The program addresses the need for more skilled cybersecurity professionals, and those who are supporting public services such as elections. This paper provides an overview of the key components of the program: a full semester gateway course covering sociotechnical election topics, a two-day kickoff bootcamp to prepare students for their internship, an internship with an election office, and a one-day debrief and assessment at the end of the internship.
Keywords: cybersecurity; elections; security education; experiential learning; service learning